The Aquanaut - Santat, Dan 1975- (Graphix, an imprint of Scholastic, 2022)
"Ever since her father was lost at sea, Sophia has been moping around Aqualand, a marine theme park. But Sophia's world is turned upside-down when an "aquanaut" breaks into the park's research lab. To her amazement, Sophia discovers that the aquanaut is not what it seems: inside lives a band of goofy sea creatures! And when they all realize that Aqualand is more sinister than advertised, Sophia is determined to help the aquanaut crew free the park's captive marine life before it's too late."--Front jacket flap
Keywords: Amusement parks -- Comic books, strips, etc; Marine animals -- Comic books, strips, etc; Girls -- Comic books, strips, etc; Meerestiere; Freizeitpark; Bedrohte Tiere; Mädchen -- 10-13 Jahre; Orphans / Fiction; Endangered species / Conservation / Fiction; Cartoons and comics; Amusement parks; Girls; Marine animals; Children's stories; Juvenile works; Fiction; Fiction 9+; Picture Books for Older Readers; Comic; Comics (Graphic works); Graphic novels; Humorous fiction; Science fiction